Biosolids leachate variability, stabilization surrogates, and optical metric selection. Issue 3 (10th February 2022) - Fischer, Sarah J.; Gonsior, Michael; Chorover, Jon; Powers, Leanne C.; Hamilton, Amanda; Ramirez, Mark; Torrents, Alba
Abstract : Sludge and biosolids organic matter (OM) are increasingly assessed via optical measurements of associated leachates – especially at pilot and bench scales. Abstract : Sludge and biosolids organic matter (OM) are increasingly assessed via optical measurements of associated leachates – especially at pilot and bench scales. Limited work has systematically characterized optical and size exclusion chromatography (SEC) based properties of leachable OM from full-scale solid stabilization processes, however. In this study, leachable OM of biosolids from nine full-scale facilities with lime treatment (LT), anaerobic digestion, or aerobic digestion (AeD) ( n = 3 facilities per type), was sampled for three sampling dates per facility and multiple extractions per biosolid ( n = 54 leachates). Leachates were characterized by high-performance size exclusion chromatography (HP-SEC-UV), ultraviolet (UV)-visible absorbance spectra, and excitation emission matrix (EEM) spectroscopies, pH, and leachable DOC/kg solid. AnD and AeD biosolids-DOM consistently exhibited higher molecular weight DOM (1360 Da) and fluorescence emissions >380 nm after digestion. This suggested higher molecular-weight, heterogeneous OM is released into soluble phases after biological treatment. Fluorescent emission peaks >450 nm were present only in AnD-biosolids leachates ( n = 27), providing a consistent signature for anaerobically digested material. Given the agreement of these trends with pilot scale studies, strategies detecting fluorescence emissions >380 nm are proposed stabilization surrogates at full-scale facilities. Prior to this study, there was limited literature consensus for which optical metrics best quantified sludge and biosolids-DOM transformations, however. Critical analysis of ten optical metrics indicated that not all pre-established metrics captured unique spectral differences in biosolids-DOM spectra, as optical metrics were first developed for aquatic DOM. Absorption ( E 2  :  E 3, SUVA254, S R ), and fluorescence metrics (HIX, BIX, and fluorescence regional integration (FRI)) were less adaptable to biosolids-DOM spectra. Principal component analysis (PCA) confirmed that targeted peak ratio assessment ( i.e. B : T or A : C peak maxima analysis) best differentiated intrinsic fluorescent DOM changes by treatment. Three independent parallel factor analysis (PARAFAC) models for major treatment types of LT, AnD, and AeD biosolids-DOM also validated treatment differences captured by peak picking surrogates. PARAFAC models described new components in the OpenFluor spectral database. Overall, targeted fluorescence peak picking represents a surrogate strategy to monitor leachate quality changes across full-scale treatment trains. These findings may advance optical approaches for process engineering and advanced stabilization research.